2020
DOI: 10.3390/cancers12113449
|View full text |Cite
|
Sign up to set email alerts
|

Nimotuzumab Site-Specifically Labeled with 89Zr and 225Ac Using SpyTag/SpyCatcher for PET Imaging and Alpha Particle Radioimmunotherapy of Epidermal Growth Factor Receptor Positive Cancers

Abstract: To develop imaging and therapeutic agents, antibodies are often conjugated randomly to a chelator/radioisotope or drug using a primary amine (NH2) of lysine or sulfhydryl (SH) of cysteine. Random conjugation to NH2 or SH groups can require extreme conditions and may affect target recognition/binding and must therefore be tested. In the present study, nimotuzumab was site-specifically labeled using ∆N-SpyCatcher/SpyTag with different chelators and radiometals. Nimotuzumab is a well-tolerated anti-EGFR antibody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Currently, 225 Ac radiopharmaceuticals are typically paired with alternative imageable isotopes including 68 Ga, 177 Lu, 111 In, and 89 Zr (Baum and Kulkarni 2012, Kratochwil et al 2016, Kelly et al 2020, Solomon et al 2020. 177 Lu has been used for intra-therapy dosimetry of 225 Ac as it is often administered in tandem therapies (Khreish et al 2020, Rosar et al 2021.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, 225 Ac radiopharmaceuticals are typically paired with alternative imageable isotopes including 68 Ga, 177 Lu, 111 In, and 89 Zr (Baum and Kulkarni 2012, Kratochwil et al 2016, Kelly et al 2020, Solomon et al 2020. 177 Lu has been used for intra-therapy dosimetry of 225 Ac as it is often administered in tandem therapies (Khreish et al 2020, Rosar et al 2021.…”
Section: Discussionmentioning
confidence: 99%
“…Due to a lack of an element-equivalent imageable isotope of 225 Ac, performance evaluation of 225 Ac radiopharmaceuticals is currently assessed by either performing invasive organ-harvesting biodistribution studies in preclinical models. In clinical settings, 225 Ac radiopharmacuticals are paired with an imageable isotope, such as 68 Ga (Baum and Kulkarni 2012), 177 Lu (Kratochwil et al 2016), 111 In (Kelly et al 2020) and 89 Zr (Solomon et al 2020). Absorbed dose is inferred with the underlying assumption of equivalent uptake and residency between 225 Ac and imageable forms of a radiopharmaceutical using other isotopes.…”
Section: Introductionmentioning
confidence: 99%
“…N4MU01 was conjugated with p -SCN-Bn-deferoxamine (DFO) for labeling with 89 Zr as described previously [22]. Quality control of the immunoconjugate was done using size exclusion chromatography (SEC) high-performance liquid chromatography (HPLC) (SEC-HPLC), flow cytometry, and automated electrophoresis (2100 Bioanalyzer, Agilent, Santa Clara, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Quality control of the immunoconjugate was done using SEC-HPLC, matrix-assisted laser desorption (MALDI) time of flight (TOF) (MALDI-TOF) and flow cytometry. Radiolabeling with 225 Ac was performed as previously reported [22].…”
Section: Conjugation With Bifunctional Chelators and Radiolabeling Wi...mentioning
confidence: 99%
“…The calculated absorbed dose of [ 89 Zr]Zr-nimotuzumab was lower than what was earlier estimated for [ 89 Zr]Zr-DFO-panitumumab [ 121 ], suggesting that [ 89 Zr]Zr-nimotuzumab might be a promising alternative to panitumumab and also cetuximab [ 123 ]. A recent study also reported 89 Zr labeling of nimotuzumab with a SpyTag/SpyCatcher, which would also enable labeling with 225 Ac for radioimmunotherapy [ 124 ]. Currently, [ 89 Zr]Zr-nimotuzumab is investigated in a phase I/II trial to determine its diagnostic quality in lung and colorectal cancer patients (NCT04235114).…”
Section: Her1 Imagingmentioning
confidence: 99%